Elizabeth Gilbert's Self-Healing Efforts from Past Trauma in the Novel Eat Pray Love - Naafi'atun (Lakon : Jurnal Kajian Sastra dan Budaya, 2022)
This study aims to determine the symptoms of trauma experienced by Elizabeth Gilbert and how Gilbert's efforts to reconcile her trauma. The data source used in this study is the novel Eat Pray Love. While the method used in this research is descriptive analysis method. The theory used to examine the symptoms of trauma and Elizabeth Gilbert's reconciliation efforts is the trauma theory by Cathy Caruth and the concept of acting out and working through from LaCapra. The data analysis technique was carried out by reading the novel Eat Pray Love, classifying the data into tables based on predetermined variables, analyzing the data, and finally writing conclusions. The results of this study are the symptoms that appear in response to the traumatic events experienced by Gilbert such as symptoms of fear, anxiety, depression, and the desire to hurt oneself to the desire to commit suicide. In an effort to reconcile his trauma, Gilbert travels to three countries, avoids things that are potentially traumatic, and testifies by writing novels based on his life experiences.